2004
DOI: 10.3346/jkms.2004.19.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Aberrantp16INK4AMethylation in Sera of Patients with Liver Cirrhosis and Hepatocellular Carcinoma

Abstract: Hepatocellular carcinomas (HCCs) show genomic alterations, including DNA rearrangements associated with HBV DNA integration, loss of heterozygosity, and chromosomal amplification. The genes most frequently involved are those encoding tumor suppressors. The p16INK4A tumor suppressor gene frequently displays genetic alteration in HCC tissues. The present study was performed to examine the incidence of methylated p16INK4A in the sera of liver cirrhosis (LC) and HCC patients, and to evaluate its role as a tumor ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 23 publications
1
27
0
2
Order By: Relevance
“…Wong et al (18) reported a good correlation between p16 hypermethylation in HCC tissues and plasma/ serum DNA (72%) and that p16 hypermethylation was not detected in the plasma/serum of patients with either liver cirrhosis or hepatitis. However, in another study, 17% of cirrhosis patients had serum DNA with aberrant p16 methylation (22). These differing results may be due to the lack of standardized processing of blood samples and methods of analysis; the relatively small sample size and diversity in the clinical courses of patients may also contribute to the variation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Wong et al (18) reported a good correlation between p16 hypermethylation in HCC tissues and plasma/ serum DNA (72%) and that p16 hypermethylation was not detected in the plasma/serum of patients with either liver cirrhosis or hepatitis. However, in another study, 17% of cirrhosis patients had serum DNA with aberrant p16 methylation (22). These differing results may be due to the lack of standardized processing of blood samples and methods of analysis; the relatively small sample size and diversity in the clinical courses of patients may also contribute to the variation.…”
Section: Discussionmentioning
confidence: 85%
“…Another possibility was that some ''normal controls'' have cryptogenic hepatic cirrhosis. A small percentage of patients with liver cirrhosis were reported to be positive for p16 methylation in serum DNA (22), but these changes still need further study. In the present study, the 50 cases were randomly selected.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified numerous epigenetic changes, such as promoter CpG island methylation, that are responsible for inactivation of tumor suppressor genes (38)(39)(40)(41). Gene expression profiles of HCCs with different etiology show different molecular signatures (42,43), suggesting that heterogeneous hepatocarcinogenetic pathways, involved in cell proliferation, cell cycle, apoptosis, and angiogenesis, exist and are deregulated in hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, many of these most widely investigated markers are not suitable for specific detection of a particular disease. For example, methylation of the gene CDKN2a (p16) has been reported to be found in blood from patients with numerous types of cancer including oral cancer, gastric cancer, melanoma, nonsmall-cell lung cancer, hepatocellular cancer, and bladder cancer in a number of independent studies (17)(18)(19)(20)(21)(22). Clearly, methylation of this gene is important in neoplastic progression, but its usefulness as a specific marker for a single cancer in a screening application is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, methylation of this gene is important in neoplastic progression, but its usefulness as a specific marker for a single cancer in a screening application is questionable. Furthermore, CDKN2a has been shown to be methylated in blood from individuals with noncancerous diseases, albeit at a lower rate (21,23).…”
Section: Introductionmentioning
confidence: 99%